Big Five Personality Traits and executive meta-competencies: Implications for Strategic decision making - Fauzan Fadli; Nazifah Husainah; Maswanto Maswanto (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the relationship between Big Five Personality Traits and strategic decision-making effectiveness at the executive level, while exploring the role of intrinsic meta-competencies that emerge when leaders face moments of isolation and make decisions independently. Methodology/approach: Using a mixed-methods design, the study applies Braun and Clarke’s thematic analysis and Interpretative Phenomenological Analysis (IPA). Data sources include Big Five personality assessments of 50 senior executives and in-depth interviews with eight directors from various strategic industries. Results: Findings reveal that openness to experience and conscientiousness consistently correlate with reflective, structured, and visionary decision-making patterns. The study also identifies that intrinsic meta-competencies such as productive solitude, deep reflection, and resilience in isolation enhance the positive manifestation of these personality traits. Conclusion: The research provides a conceptual foundation for developing a more holistic talent development and succession planning framework, integrating personality traits and internal capacities often overlooked in leadership assessments. Limitations: The study focuses on senior executives in strategic industries, limiting generalizability to other leadership levels or sectors. Additionally, qualitative methods may introduce subjective interpretations. Contribution: This study contributes to leadership psychology and talent management by highlighting the interplay between personality, meta-competencies, and decision-making. It offers practical insights for executive coaching, leadership development programs, and organizational succession planning.